2020
DOI: 10.1111/apa.15424
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review suggests a relationship between moderate to late preterm birth and early childhood caries

Abstract: Aim: The aim was to examine the association between moderate to late preterm birth and the prevalence of early childhood caries. Methods: We searched the PubMed, Scopus, Cochrane Trials Register databases up to February 28, 2020. Two independent reviewers screened the papers for relevance, extracted data and assessed the risk of bias. A random-effects meta-analysis was performed to pool the prevalence of early childhood caries by gestational age. Results: The authors identified 14 studies covering 210,691 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Vaginal-born children are 2.27 times more likely to experience ECC compared to their counterparts. These findings are consistent with those evidenced in earlier studies ( Pattanaporn et al., 2013 ; Twetman et al., 2020 ). What is not yet clear is how those plausible caries-associated risk factors impact on oral microbial composition in 2- to 3-year-old children.…”
Section: Discussionsupporting
confidence: 94%
“…Vaginal-born children are 2.27 times more likely to experience ECC compared to their counterparts. These findings are consistent with those evidenced in earlier studies ( Pattanaporn et al., 2013 ; Twetman et al., 2020 ). What is not yet clear is how those plausible caries-associated risk factors impact on oral microbial composition in 2- to 3-year-old children.…”
Section: Discussionsupporting
confidence: 94%
“…We found no significant difference in caries prevalence between preterm– and full term–born children, as showed by many others [ 6 , 8 11 ]. However, other studies showed the contrary [ 12 , 13 ]. It is important to consider though, that the dental caries indexes used in this study, were calculated in Sweden without evaluating missing teeth.…”
Section: Discussionmentioning
confidence: 94%
“…During the preschool and school years, it has been shown that preterm-born patients had more DBMP during dental examinations and treatment than children born full term [6,7], as well as a higher number of missed appointments during the preschool years [6]. Nevertheless, some studies have shown that preterm-born children did not have a higher risk of developing caries lesions than full term-born children [6,[8][9][10][11] while others have shown the opposite [12,13]. Other reported oral health problems in preterm-born children (especially in extremely preterm-and very preterm-born children) include disturbances in tooth development, such as smaller teeth, delay in tooth maturation, and more enamel defects compared with full term-born children.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta‐analysis by Tweetman et al 7 found a significantly higher prevalence of early childhood caries in children born moderate to late preterm than full term. The authors identified 14 studies of 210 691 children, published from 2007 to 2020.…”
Section: Systematic Review Suggests a Link Between Moderate To Late Pmentioning
confidence: 99%